The impact of electronic system usage in insurance company / Anies Athirah Awang Mohamad Zaid - Awang Mohamad Zaid, Anies Athirah (Faculty of Business and Management, 2015)
In this study, it will analyze the impact that affecting electronic system usage in insurance company at Lonpac Insurance Berhad, Jalan Sultan Sulaiman. The insurance sector in Malaysia has shown rapid growth in recent years. However, the annual report of Lonpac Insurance Berhad that showing the statistic number of policy issued in underwriting department stated that there have a decreasing amount on issuing policy insurance on previous 3 years, from 2012 until 2014.